2016
DOI: 10.5114/jcb.2016.61704
|View full text |Cite
|
Sign up to set email alerts
|

Y-configured metallic stent combined with 125 I seed strands cavity brachytherapy for a patient with type IV Klatskin tumor

Abstract: We report a case in an inoperable patient with type IV Klatskin tumor treated by the use of a novel, two piece, Y-configured self-expandable metallic stent (SEMS) combined with two 125I seed strands via bilateral approach. The placement of the Y-shaped SEMS was successful and resulted in adequate biliary drainage. After 2 months of intraluminal brachytherapy (ILBT), both 125I seed strands and temporary drainage catheter were removed after patency of the expanded stents was confirmed by the cholangiogram. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Secondly, this approach delivers high doses of radiation to localized tumors with limited systemic side effects. Thirdly, this approach represents a form of conformal radiotherapy that is associated with improved accuracy because of patient movement [24]. The mainstay treatment method of intracavitary radiotherapy consists of 125 I stranded seeds and irradiation stents, all of which show efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, this approach delivers high doses of radiation to localized tumors with limited systemic side effects. Thirdly, this approach represents a form of conformal radiotherapy that is associated with improved accuracy because of patient movement [24]. The mainstay treatment method of intracavitary radiotherapy consists of 125 I stranded seeds and irradiation stents, all of which show efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of stent dysfunction were unclear. In addition, irradiation stents cannot be immediately withdrawn in any instance, as intracavitary brachytherapy-related complications can occur [6,24]. In our department, 58 patients diagnosed with MBO were enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12-14 125 I seeds strands have also been applied to treat MBO, 15,16 however, the use of 125 I radioactive particles in hilar MBO has rarely been described. [17][18][19] The aim of the present study was to perform retrospective analyses of the effectiveness and safety of SEMS combined with 125 I seeds strand in the treatment of patients with Bismuth type I-IV hilar MBO.…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 125 I seeds strands have also been applied to treat MBO, 15 , 16 however, the use of 125 I radioactive particles in hilar MBO has rarely been described. 17 19 …”
Section: Introductionmentioning
confidence: 99%
“…There are no clear recommendations regarding how to reopen SEMS occlusions. Recently, some studies reported the safety and efficacy of a Habib EndoHPB percutaneous radiofrequency ablation (PRFA) catheter for re-opening occluded SEMSs, with a median stent patency time of 102-234 days (4-9).We previously showed that intraluminal brachytherapy (ILBT) with low dose rate (LDR) iodine-125 ( 125 I) seed strands is effective for treatment of malignant biliary obstruction, prolonging stent patency (10,11). To the best of our knowledge, there are no reports regarding the use of PRFA and ILBT synchronously to re-open SEMS occlusions.…”
mentioning
confidence: 99%